Perception of Medical Staff Performance by Patients in Al-Ramadi Hospitals - Yaseen T. Sarhan (Karbala Journal of Medicine, 2025)
Background: Patients' perceptions regarding physician's performance and communication abilities can serve as a valuable indicator of the quality of healthcare services rendered. This study aims to evaluate the performance of medical staff in Al-Ramadi Hospitals from the viewpoint of patients. Methods: A cross-sectional study was conducted from 7 December 2022, to 29 January 2023, at Al-Ramadi Teaching Hospital and the Maternity and Child Teaching Hospital, encompassing both public and private sectors. A random sample of 150 patients (67 males and 83 females) was selected for participation. Data collection was facilitated through a structured questionnaire that gathered socio-demographic information alongside details pertinent to the hospital stay. Results: The average age of the participants was 43.5±19.7 years. Males and females represent 44.7% and 55.3% of the total patients, respectively. A bout 68.0% of participants evaluated the overall performance of the medical staff as agree, while 26.7% rated it as neutral, 4.0% as disagree, and only 1.3% considered their performance and communication skills to be strongly agree. Conclusions: Patients rated the performance and communication abilities of physicians as satisfactory. Keywords: AL-Ramadi Hospitals, Patients perception, Staff performance..